Peran Guru PAK dalam Meneladankan Akhlak Mulia Kepada Siswa di SMPN 1 Lahomi, Nias Barat - Nuriksfani Daeli (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
Challenges faced by Christian Religious Education (PAK) teachers in dealing with the diversity of student backgrounds that affect the acceptance of the values ​​taught This study examines the role of Christian Religious Education (PAK) teachers in providing examples through noble morals to students at SMP Negeri 1 Lahomi, West Nias Regency. The noble morals possessed by a PAK teacher play an important role in shaping students' character, especially in the context of religious education that emphasizes moral and spiritual values. This study uses a qualitative literature method. Data were collected through document analysis related to learning activities and teacher interactions with students. The results of the study indicate that PAK teachers at SMP Negeri 1 Lahomi provide strong examples through noble morals in various aspects, such as patience, honesty, discipline, and compassion. PAK teachers also use an approach based on religious values ​​to guide students in developing good character. This study concludes that strengthening PAK teachers to provide examples in developing noble morals has an impact on students in creating themselves as role models for others.